2014
DOI: 10.4103/0972-5229.126087
|View full text |Cite
|
Sign up to set email alerts
|

Severe methemoglobinemia due to insecticide poisoning

Abstract: Methemoglobinemia is an altered state of hemoglobin resulting in impaired oxygen delivery to the tissues. Deliberate ingestion of certain insecticides and pesticides may result in this condition. We report a case of severe methemoglobinemia after deliberate ingestion of an insecticide marketed to be safe and containing only biological extracts and fillers. Methemoglobinemia should be suspected with low oxygen saturation on pulse oxymetry and the presence of chocolate colored blood. The methemoglobin level of 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 4 publications
1
17
1
2
Order By: Relevance
“…Severe methemoglobinemia (MetHb>70%) is usually fatal, as evidenced in our first case though survival has been reported with a MetHb level of 80% in our case2 and previous reports (4,10).…”
Section: Discussion:-supporting
confidence: 60%
See 1 more Smart Citation
“…Severe methemoglobinemia (MetHb>70%) is usually fatal, as evidenced in our first case though survival has been reported with a MetHb level of 80% in our case2 and previous reports (4,10).…”
Section: Discussion:-supporting
confidence: 60%
“…The clinical manifestations (Table I) of methemoglobinemia are due to impaired oxygen delivery to the tissues and hence correlate with severity of methemoglobinemia. The onset of signs and symptoms in our cases was 30-60 minutes after pesticide ingestion.We observed bilateral pin point pupils in two cases and positive troponin and myoglobin in one case but this finding was not seen with similar poisoning described by George et al (4).…”
Section: Discussion:-contrasting
confidence: 59%
“…However, search has shown that biological extracts are known to be rich in nitrogenous products and may potentially cause methemoglobinemia. 6 In our patient, diagnosis of methemoglobinemia was made on triad of saturation gap, cyanosis, and dark blood. Early recognition and on symptomatic treatment led to recovery with normal neurological function.…”
Section: Discussionmentioning
confidence: 78%
“…Acquired Methemoglobinemia occurs as a result of many drugs with oxidizing effects and when methemoglobins are more than the reductive capacity of the Generally 10%-20% of methemoglobin levels are well tolerated and the symptoms are usually detected when the levels are more than 20%. Methemoglobinemia levels higher than 70% may lead to coma and death [4,5].…”
Section: Discussionmentioning
confidence: 99%